Surgical outcomes in adolescents and adults with anomalous aortic origin of a coronary artery - Li, Baotong; Ding, Li; Sun, Hansong (Frontiers in Cardiovascular Medicine, 2024)
BackgroundAnomalous aortic origin of a coronary artery (AAOCA) is associated with an increased risk of myocardial ischemia and sudden cardiac death. This study aims to evaluate the medium-term outcomes of surgical repair for AAOCA and to introduce a novel off-pump technique for anomalous coronary artery reimplantation.MethodsWe retrospectively reviewed the medical records of 12 patients aged 12 years and older who underwent AAOCA surgery at Fuwai Hospital between 2009 and 2016.ResultsThe median age at surgery was 26 years (range, 13–57 years). Patients with an anomalous left coronary artery from the right sinus (ALCA-R) were significantly younger than those with an anomalous right coronary artery from the left sinus (ARCA-L) (P < 0.001). During a median follow-up of 13 years (range, 8–15years), 11 patients had widely patent repaired coronary arteries, with the exception of one patient (case 5) who experienced occlusion of the left internal mammary artery graft 1 year post-CABG. The incidence of postoperative cardiac-type symptoms (angina, syncope or dyspnea) was higher in ALCA-R patients compared to ARCA-L patients. Patch angioplasty using a pulmonary artery patch and RCA reimplantation without cardiopulmonary bypass yielded satisfactory medium-term outcomes.ConclusionsCompared with ARCA-L, the incidence of postoperative cardiac-type symptoms was higher in ALCA-R patients. Properly selected surgical procedures can lead to successful outcomes in patients with AAOCA. Patch angioplasty with a pulmonary artery patch and RCA reimplantation without cardiopulmonary bypass are viable and effective surgical options. CABG may not be the preferred surgical approach for AAOCA.